Nutrition-Related Content on Instagram in the United States of America: Analytical Cross-Sectional Study - Hector José Tricas-Vidal; María Concepción Vidal-Peracho; María Orosia Lucha-López; César Hidalgo-García; Ana Carmen Lucha-López; Sofía Monti-Ballano; Jaime Corral-de Toro; Sergio Márquez-Gonzalvo; José Miguel Tricás-Moreno (Foods, 2022)
Background: The Internet is today the largest platform for food distribution, and there are concerns about the impact that digital marketing has in the field of nutrition by promoting non-evidence-based recommendations. The purpose of this study was to describe the user profile that draws on Instagram to follow nutrition-related content versus not, and to analyze the frequency and type of content of the information provided by nutritional influencers. Methods: A cross-sectional study involving randomly selected United States residents having an Instagram account was performed. Participants completed an anonymous online survey link. Results: From 898 respondents, 78.7% were women, and 75.6% were Millennials. Scientific evidence present in the posts was 14.3%. Influencers promoted a product or a brand in more than 90% of posts. Women followed more nutrition-related content than men (p < 0.001). Millennials, followed by Generation-Z, followed more nutrition-related content (p < 0.001). There were no significant relationships between the following status of nutrition-related content with BMI, type of job, household income, education degree, or smoking habits. Conclusions: Women and Millennials followed more nutrition-related content. Scientific evidence was scarce and commercial interest in the network was evident. The vast majority of the posts were not based on scientific evidence and instead promoted a product/supplement.